Trypanosoma cruzi extracts elicit protective immune response against chemically induced colon and mammary cancers. Issue 7 (20th November 2015) - Ubillos, Luis; Freire, Teresa; Berriel, Edgardo; Chiribao, María Laura; Chiale, Carolina; Festari, María Florencia; Medeiros, Andrea; Mazal, Daniel; Rondán, Mariella; Bollati‐Fogolín, Mariela; Rabinovich, Gabriel A.; Robello, Carlos; et al.
Abstract : Trypanosoma cruzi, the protozoan parasite that causes Chagas' disease, has anticancer effects mediated, at least in part, by parasite‐derived products which inhibit growth of tumor cells. We investigated whether immunity to T. cruzi antigens could induce antitumor activity, using two rat models which reproduce human carcinogenesis: colon cancer induced by 1, 2‐dimethylhydrazine (DMH), and mammary cancer induced by N ‐nitroso‐ N ‐methylurea (NMU). We found that vaccination with T. cruzi epimastigote lysates strongly inhibits tumor development in both animal models. Rats immunized with T. cruzi antigens induce activation of both CD4 + and CD8 + T cells and splenocytes from these animals showed higher cytotoxic responses against tumors as compared to rats receiving adjuvant alone. Tumor‐associated immune responses included increasing number of CD11b/c + His48 − MHC II + cells corresponding to macrophages and/or dendritic cells, which exhibited augmented NADPH‐oxidase activity. We also found that T. cruzi lysate vaccination developed antibodies specific for colon and mammary rat cancer cells, which were capable of mediating antibody‐dependent cellular cytotoxicity (ADCC) in vitro . Anti‐ T. cruzi antibodies cross‐reacted with human colon and breast cancer cell lines and recognized 41/60 (68%) colon cancer and 38/63 (60%) breast cancer samples in a series of 123 human tumors. Our results suggest that T. cruzi antigens can evoke an integrated antitumor response involving both the cellular and humoral components of the immune response and provide novel insights into the understanding of the intricate relationship between parasite infection and tumor growth. Abstract : What's new? The Trypanosoma cruzi parasite, the cause of Chagas' disease, naturally antagonizes cancer, a phenomenon discovered in the 1930s. Yet, despite decades of research, precisely how the parasite prevents tumor growth is not fully understood. Here, vaccination with T. cruzi epimastigote lysates was found to trigger strong cytotoxic responses against tumors, with activation of CD4+ and CD8+ T cells and augmented NADPH‐oxidase activity, in rats developed to recapitulate colonic and mammary carcinogenesis. In rat tumor cells, the antigens stimulated the production of antibodies that cross‐reacted with human colon and breast cancer tissue samples.